Tingkat Pendidikan, Pengalaman, Lingkungan Kerja Sebagai Determinan Kinerja Karyawan BPCB DIY - Anugrah Pangesti; Wuku Astuti; Bhenu Artha (Departement of Mathematics Education, 2024)
Accountability is expected to improve employee performance in the public sector. Government agency employees are required to have high work quality and professionalism in order to change people's views by providing good, transparent and accountable service. This research is quantitative research, located at BPCB D.I. Yogyakarta. The population in this study were all BPCB DIY employees, totaling 400 employees. The sample used was 80 respondents, using simple probability sampling. Questionnaires and observations were used to collect data. The data was processed using multiple linear regression to analyze the data. The research results show that the level of influence has a partial effect on the performance of BPCB DIY employees, work experience has a partial effect on the performance of BPCB DIY employees, the work environment has a partial effect on the performance of BPCB DIY employees. Level of education, work experience and work environment simultaneously influence the performance of BPCB DIY employees.